2020
DOI: 10.1016/j.hrthm.2020.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Ostial dimensional changes after pulmonary vein isolation: Pulsed field ablation vs radiofrequency ablation

Abstract: BACKGROUND Pulmonary vein (PV) stenosis is an important potential complication of PV isolation using thermal modalities such as radiofrequency ablation (RFA). Pulsed field ablation (PFA) is an alternative energy that causes nonthermal myocardial cell death.OBJECTIVE The purpose of this study was to compare the effect of PFA vs RFA on the incidence and severity of PV narrowing or stenosis.METHODS Data were analyzed from 4 paroxysmal atrial fibrillation ablation trials using either PFA or RFA; because of absent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…Pulsed field ablation (PFA) is a nonthermal energy modality that is unique in having tissue-selective ablative properties. [1][2][3][4][5][6][7] Using a custom PFA generator able to deliver a custom hierarchical pulse sequence, a dedicated PFA catheter was shown to be safe and effective in electrically isolating porcine thoracic vessels-pulmonary veins (PVs) and superior vena cava. Histological analysis demonstrated similar transmurality to radiofrequency ablation, but without the attendant collateral injury.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed field ablation (PFA) is a nonthermal energy modality that is unique in having tissue-selective ablative properties. [1][2][3][4][5][6][7] Using a custom PFA generator able to deliver a custom hierarchical pulse sequence, a dedicated PFA catheter was shown to be safe and effective in electrically isolating porcine thoracic vessels-pulmonary veins (PVs) and superior vena cava. Histological analysis demonstrated similar transmurality to radiofrequency ablation, but without the attendant collateral injury.…”
Section: Introductionmentioning
confidence: 99%
“…It was evident that no PV stenosis arose due to IRE-exposed subjects at 3-month follow-up, while those who underwent RF ablation exhibited stenosis immediately that persisted for the follow-up survival period [ 89 ]. In recent years, the effects of IRE and RF were investigated in humans and research showed that the incidence of stenosis and narrowing of PV diameter following PFA was virtually eliminated (0%), while patients who received RF energy saw a 12.0% reduction in diameter and 32.5% incidence of stenosis at 3-month follow-up [ 90 ].…”
Section: Electroporation As An Ablative Approachmentioning
confidence: 99%
“…Thus, the absolute requirement for synchronization is unclear. The use of IRE requires meticulous monitoring of blood pressure and electrolytes, as instances of induced mild hypertension and epileptic-like seizures have been reported with the use of high voltages and general anaesthesia during IRE procedures [ 81 , 90 , 101 ]. Cases of such intraoperative complications could jeopardize patient safety, therefore a clear understanding and rapid, appropriate management by the clinician is paramount.…”
Section: Electroporation As An Ablative Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous preclinical studies have demonstrated its ability to spare the esophagus and phrenic nerve during ablation, 1 and first-in-human research showed that it has no effect on the diameter of the pulmonary veins following ablation. 2 Its short-term efficacy has also been demonstrated with a high rate of acute pulmonary vein isolation, which was also proven to be durable based on remapping studies. 3 Moreover, PFA appears to be an efficient modality, with very short procedure times.…”
mentioning
confidence: 99%